2020
DOI: 10.1155/2020/4871814
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Venous Bypass Graft Pseudoaneurysm with the New Solaris Self-Expanding Covered Stent

Abstract: Nonanastomotic pseudoaneurysm formation after vascular reconstruction is a rarely encountered problem. Covered stent graft constitutes a minimal approach. To our knowledge, the present study constitutes the first case of implantation of Solaris stent graft in Europe. A 69-year-old man with severe cardiac dysfunction presented a pseudoaneurysm of a popliteal to popliteal artery reversed saphenous vein bypass graft. The patient was successfully treated by the percutaneous placement of a Solaris self-expanding co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…In conjunction with radial compliance, known as an essential design property for a vascular implant, successful mimicking of natural artery behavior relies on the incorporation of other elements such as nonlinearity and anisotropy. [50] The use of polymer-based fabrics or laminates in endovascular grafts evolved from their applications in open surgical repair, where either woven fabrics using fabrication technologies like weaving, [51] knitting, [52,53] braiding, [54,55] or nontextile fabrics through extrusion forming [56] and electrospinning [57,58] have been employed. Based on the fabrication technology, the material and design of the graft can differ.…”
Section: Graft Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In conjunction with radial compliance, known as an essential design property for a vascular implant, successful mimicking of natural artery behavior relies on the incorporation of other elements such as nonlinearity and anisotropy. [50] The use of polymer-based fabrics or laminates in endovascular grafts evolved from their applications in open surgical repair, where either woven fabrics using fabrication technologies like weaving, [51] knitting, [52,53] braiding, [54,55] or nontextile fabrics through extrusion forming [56] and electrospinning [57,58] have been employed. Based on the fabrication technology, the material and design of the graft can differ.…”
Section: Graft Designmentioning
confidence: 99%
“…Covered stents can be effective in the treatment of conditions like fistulae, congenital vascular disease, neurovascular disease, and coarctation of the aorta. [58,95,96] To prevent restenosis in smaller arteries, covered stents can act as an effective drug delivery platform for the localized release of therapeutic agents.…”
Section: Covered Stents and Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lesion is known as a pseudoaneurysm because there is no normal three-layer structure of arteries [1]. Pseudoaneurysm can, if left untreated, become a life-threatening situation by thrombosis, rupture, or distal embolization [2]. Thus, proper and timely treatment is very important.…”
Section: Introductionmentioning
confidence: 99%
“…2 In contrast, very few studies have demonstrated the utility of endovascular therapy for vein bypass graft pseudoaneurysm. 3 The clinical usefulness of stents in infrainguinal vein grafts is not yet established, and their safety and efficacy remain unclear. However, the case we have described, as evidenced in Panel C, demonstrates the utility of such a stent in the infrainguinal region, even for pseudoaneurysms with unusual shapes.…”
mentioning
confidence: 99%